2015
DOI: 10.1515/amm-2015-0222
|View full text |Cite
|
Sign up to set email alerts
|

Natural Aging Behavior Of Friction Stir Welded Al-Zn-Mg-Cu Aluminum Alloys

Abstract: The long term natural aging behavior of friction stir welded aluminum 7136-T76 and 7042 T6 extrusions was investigated. The microstructural characteristics and mechanical properties in the as-welded and six years naturally aged conditions were studied and correlated to a coupled thermal/material flow model of the joining process. Hardness profiles for the 7136 alloy taken along the mid-plane thickness of the workpiece displayed the characteristic W-shape. With natural aging, hardness recovery occurred on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…Kalemba et al (2015) supportFuller et al (2010) results by showing the effect of natural ageing on AA7136 and AA7042. Here it was shown that natural ageing increases the tensile and hardness properties of the material, although the 'W' shape commonly found in 7xxx series alloy hardness plots was not altered Threadgill et al (2009).…”
supporting
confidence: 80%
“…Kalemba et al (2015) supportFuller et al (2010) results by showing the effect of natural ageing on AA7136 and AA7042. Here it was shown that natural ageing increases the tensile and hardness properties of the material, although the 'W' shape commonly found in 7xxx series alloy hardness plots was not altered Threadgill et al (2009).…”
supporting
confidence: 80%
“…The friction stir welding (FSW) method, which was invented at The Welding Institute, Cambridge, UK, is a modern technology, enabling the welding and processing of various metallic materials [ 1 , 2 , 3 , 4 ]. FSW works by using a non-consumable tool to rotate and plunge into the interface of two workpieces.…”
Section: Introductionmentioning
confidence: 99%
“…It is influenced by the welding parameters, type of tool, position of the materials in the joint (in the case of dissimilar weld seams), etc. [1,2]. One of the difficulties with the FSW process is that each of these factors has a major impact on the quality of a joint.…”
Section: Introductionmentioning
confidence: 99%